2021
DOI: 10.1119/10.0004957
|View full text |Cite
|
Sign up to set email alerts
|

The Newcomb–Benford law: Scale invariance and a simple Markov process based on it

Abstract: The Newcomb–Benford law, also known as the first-digit law, gives the probability distribution associated with the first digit of a dataset so that, for example, the first significant digit has a probability of 30.1% of being 1 and 4.58% of being 9. This law can be extended to the second and next significant digits. This article presents an introduction to the discovery of the law and its derivation from the scale invariance property as well as some applications and examples. Additionally, a simple model of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Previous studies have investigated the presence of BL amongst the sunspot numbers and have revealed general non-compliance to the to the overabundance of numbers having digits 1, 2 and 3 as FSDs. Despite being rather long (more than 59000 records, after excluding days without data or with zero spots), the dynamic range -ratio between the largest and the smallest values of the sunspot number series is limited [Burgos and Santos (2021)]. The maximum number of sunspots recorded is 528 corresponding to August 26, 1870.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the presence of BL amongst the sunspot numbers and have revealed general non-compliance to the to the overabundance of numbers having digits 1, 2 and 3 as FSDs. Despite being rather long (more than 59000 records, after excluding days without data or with zero spots), the dynamic range -ratio between the largest and the smallest values of the sunspot number series is limited [Burgos and Santos (2021)]. The maximum number of sunspots recorded is 528 corresponding to August 26, 1870.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, this peculiar law has been effectively used to distinguish and diagnose frauds in taxing and accounting (Nigrini 1996;Nigrini & Mittermaier 1997;Geyer & Williamson 2004), and to minimize storage space and speed up calculation in computer science (Barlow & Bareiss 1985;Schatte 1988;Berger & Hill 2007). Theoretically, this law has been well explained by using a central-limit-like theorem for first digits (Hill 1995) and a simple Markov process (Burgos & Santos 2021). In mathematics, Benford's law is scale invariant (Berger et al 2008), which indicates that it is independent of any particular choice of units (Pinkham 1961).…”
Section: Introductionmentioning
confidence: 99%
“…Various experimental data have been accumulated in many fields of knowledge, attesting to the compliance with the NBL [17][18][19][20][21]. In particular, spatial invariance can have profound morphological implications in physiology, and it is well documented in the heart, lung, and brain [22].…”
Section: Introductionmentioning
confidence: 99%